Implementasi Pengembangan Bahan Ajar Berbasis Masalah untuk Meningkatkan Kemampuan Literasi Siswa - Usnida Junaeka Verawati (Social Science Academic, 2023)
Teaching materials are one of the important elements that influence the success of the learning process. One of the teaching materials used in the learning process is the module. Problem-based teaching materials are presented with steps that begin with problem exposure, problem identification, material exposure, and problem solutions. Teaching materials presented in addition to teaching materials are also equipped with student worksheets so that they support the problem-based learning process. The material in teaching materials contains mathematical literacy which is very important in learning mathematics. Mathematical literacy is the ability of students or students to formulate, apply, and interpret mathematics in various contexts, including the ability to perform mathematical reasoning and use the concept of procedures, facts, and mathematical tools, to describe, explain, and predict a phenomenon or event. The stages of teaching materials developed are in accordance with the characteristics of problem-based learning that are developed and can improve students' literacy skills